Comparative Study and Simulation of Capacitive Sensors in Microfluidic Channels for Sensitive Red Blood Cell Detection - Wei Hu; Bingxing Wu; Soumya K. Srivastava; Suat Utku Ay (Micromachines, 2022)
Microfluidics provides an indispensable platform for combining analytical operations such as sample preparation, mixing, separation/enrichment, and detection onto a single compact platform, defined as a lab-on-a-chip (LOC) device with applicability in biomedical and life science applications. Due to its ease of integration, 1D interdigital capacitive (IDC) sensors have been used in microfluidic platforms to detect particles of interest. This paper presents a comparative study on the use of capacitive sensors for microfluidic devices to detect bioparticles, more specifically red blood cells (RBCs). The detection sensitivities of 1D, 2D, and 3D capacitive sensors were determined by simulation using COMSOL Multiphysics® v5.5. A water-filled 25 μm × 25 μm PDMS microfluidic channel was used with different sizes (5–10 μm) of red blood cells passing across the capacitive sensor regions. The conformal mapping was used for translating the 1D IDC sensor dimensions into equivalent 2D/3D parallel plate capacitance (PPC) sensor dimensions, creating similar absolute sensor capacitance. The detection sensitivity of each capacitive sensor is determined, and a new 3D PPC sensor structure was proposed to improve the sensitivity for high-resolution RBC detection in microfluidic channels. Proposed 2D and 3D sensors provide a 3× to 20× improvement in sensitivity compared to the standard 1D IDC structures, achieving a 100 aF capacitance difference when a healthy RBC passes in the structure.